2017
DOI: 10.1098/rsbl.2017.0186
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and vertical species turnover in tropical birds in habitats with differing land use

Abstract: Large tracts of tropical rainforests are being converted into intensive agricultural lands. Such anthropogenic disturbances are known to reduce species turnover across horizontal distances. But it is not known if they can also reduce species turnover across vertical distances (elevation), which have steeper climatic differences. We measured turnover in birds across horizontal and vertical sampling transects in three land-use types of Sri Lanka: protected forest, reserve buffer and intensive-agriculture, from 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Nevertheless, species diversity per site (alpha diversity), as measured by rarefied richness, was actually highest in rural locations. A relatively high diversity of birds in human-modified landscapes has also been found in some recent surveys in Asia (Ranganathan et al 2008, Sreekar et al 2017, Kale et al 2018. Still, composition of species with different diet preferences was not constant over the urbanization gradient; insectivores were dominant in natural areas, as also has been shown in other studies (Bregman et al 2014, Sreekar et al 2015.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Nevertheless, species diversity per site (alpha diversity), as measured by rarefied richness, was actually highest in rural locations. A relatively high diversity of birds in human-modified landscapes has also been found in some recent surveys in Asia (Ranganathan et al 2008, Sreekar et al 2017, Kale et al 2018. Still, composition of species with different diet preferences was not constant over the urbanization gradient; insectivores were dominant in natural areas, as also has been shown in other studies (Bregman et al 2014, Sreekar et al 2015.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, niche expansion means that the overall niche space of an assemblage increases with species richness, often as a result of high productivity and structural heterogeneity (Wilson 1961, Lister 1976, Pautasso and Gaston 2006. These alternative scenarios could be relevant to gradients of human disturbance, even if species richness remains relatively high in transformed areas, as can occur in some tropical or subtropical regions (Ranganathan et al 2008, Sreekar et al 2017). If niche packing predominates, the increased redundancy between generalist species in human-made habitats may result in higher niche overlap as well as niche width, so that the overall assemblage niche space remains similar to that in natural areas (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…) particularly along elevational gradients (Sreekar et al . ). In montane parks such as CNP, the buffer zone is both more accessible to local communities and more suitable for agricultural use.…”
Section: Discussionmentioning
confidence: 97%
“…Forest edges and agropastoral mosaics do have the potential to harbor reasonable amounts of bird diversity (Ricketts et al 2001, S ßekercio glu et al 2007, Neate-Clegg et al 2016. However, more species in general are lost than gained through habitat conversion in the tropics , Mahood et al 2012, resulting in lower species turnover (Moura et al 2013, de Castro Solar et al 2015 particularly along elevational gradients (Sreekar et al 2017). In montane parks such as CNP, the buffer zone is both more accessible to local communities and more suitable for agricultural use.…”
Section: Discussionmentioning
confidence: 99%
“…A lower influence of α-diversity results in the correlation between β- and γ-diversity [ 20 ]. This potentially prevents accurate estimation of β-diversity, especially when γ-diversity varies with environmental gradients such as elevation and latitude [ 6 , 21 ]. Previous studies have shown that the influence of γ-diversity on β-diversity decreases with increasing grain size [ 6 , 22 ] and changes β-diversity patterns across broad-scale ecological gradients [ 22 ].…”
Section: Introductionmentioning
confidence: 99%